Hematological cancer patients’ social support, coping strategies, anxiety, depression and posttraumatic growth: a structural equation model - Liang, Taoyun; Mao, Ling; Du, Xinwen; Chen, Fengjiao (Frontiers in Oncology, 2025)
ObjectivePosttraumatic growth (PTG), defined as positive psychological changes following traumatic events, has been observed in some hematological cancer patients during their disease course. These changes, encompassing shifts in life perspective, interpersonal relationships, and self-perception, are critical for psychological recovery. However, the interplay of social support, coping strategies, anxiety, and depression in shaping PTG remains unclear. Therefore, the aim of this study was to explore these associations in hematological cancer patients using a hypothetical model.MethodsFrom August 2019 to May 2021, a cross-sectional survey was conducted with 474 hospitalized patients with hematological cancer at West China Hospital, Sichuan University, China (a tertiary hospital). The Social Support Rating Scale, Medical Coping Modes Questionnaire, Hospital Anxiety and Depression Scale, and Posttraumatic Growth Inventory were used for data collection. Correlation and regression analyses were performed using SPSS 26.0, a structural equation model was constructed using AMOS 24.0 software, and the confidence interval of the mediating effect was calculated using the bias-corrected bootstrap method.ResultsSocial support was positively associated with PTG in hematological cancer patients (β = 0.564, P = 0.004). Avoidance (β = 0.199, P = 0.034) and acceptance–resignation (β = -0.315, P = 0.002) coping strategies mediated this association, with depression (β = -0.123, P = 0.009) further mediating the effects of coping strategies on PTG.ConclusionThese findings provide a basis for further research on PTG in cancer patients, particularly with respect to coping strategies in various dimensions. Enhancing social support and addressing maladaptive coping may promote PTG. Tailored interventions targeting depression management and culturally sensitive support systems are recommended to enhance PTG.